Blood Pressure Control among Hypertensive Diabetic Patients on Follow-Up at Chronic Clinic of Nekemte Referral Hospital in West Ethiopia - Mohammed Gebre Dedefo; Dureti Bayisa Gemechu; Ginenus Fekadu; Tesfa Tekle Dibessa (International Journal of Hypertension)
Background. Hypertension is a prevalent comorbid condition in diabetes, affecting ∼20–60% of patients with diabetes, depending on obesity, ethnicity, and age. Adults with diabetes historically have two or three times higher rate of cardiovascular disease (CVD) than adults without diabetes. Objective. The aim of this study was to assess blood pressure (BP) control and its predictors among hypertensive diabetic patients on follow-up at the chronic clinic of Nekemte Referral Hospital (NRH) in West Ethiopia. Methods. A cross-sectional study was conducted among hypertensive adult patients comorbid with diabetes taking antihypertensive drugs for at least one year in NRH. Both bivariable and multivariable analyses were done. The odds ratio, along with 95% confidence level, was estimated to identify factors associated with uncontrolled BP by using multivariable logistic regression analysis. The level of statistical significance was declared at p value <0.05 levels. The patient’s written informed consent was obtained after explaining the purpose and procedures of the study. Results. A total of 186 study participants were included in this study. The mean age of the participants was 51.2 ± 12.2 years. Blood pressure and blood glucose were controlled in 104 (55.9%) and 106 (57.0%) study participants, respectively. In the multivariable analysis, age ≥60 years (AOR = 4.537, 95% CI = 1.142–18.024, p=0.032), duration with hypertension ≥5 years (AOR = 3.534, 95% CI = 1.062–11.760, p=0.040), cigarette smoking (AOR = 7.697, 95% CI = 2.356–25.146, p=0.001), nonadherence (AOR = 6.584, 95% CI = 2.337–18.553, p<0.001), and uncontrolled glycaemia (AOR = 21.630, 95% CI = 8.057–58.070, p<0.001) were independent predictors of uncontrolled blood pressure. Conclusion. Compared to the previous studies, BP was better controlled among hypertensive diabetic patients in the present study. Older age, longer duration with hypertension, cigarette smoking, nonadherence, and uncontrolled glycaemia were predictors of uncontrolled BP. Thus, interventions on modifiable factors should be done to improve BP control of patients’ comorbid with diabetes.